2021
DOI: 10.1186/s12979-021-00256-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-425-5p modulates osteoporosis by targeting annexin A2

Abstract: Background Studies have shown that the decrease of osteogenic differentiation of bone marrow mesenchymal stem cells (MSC) is an important mechanism of osteoporosis. The object of this study was to explore the role and mechanism of microRNA miR-425-5p in the differentiation of MSC. Methods The expression of miR-425-5p in MSC was detected by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR). Cell proliferation, cell cycle and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These findings suggest that miR-425-5p promotes value-addition in BMECs by specifically targeting and regulating TOB2. Previous investigations have also shown that miR-425-5p regulates cellular value-addition through its targeting of AFF4 and ANXA2 [23,50].…”
Section: Discussionmentioning
confidence: 89%
“…These findings suggest that miR-425-5p promotes value-addition in BMECs by specifically targeting and regulating TOB2. Previous investigations have also shown that miR-425-5p regulates cellular value-addition through its targeting of AFF4 and ANXA2 [23,50].…”
Section: Discussionmentioning
confidence: 89%
“…ANXA2 is a target of Mir-425-5p and is involved in TNF-induced apoptosis, proliferation and differentiation of MSC cells. It was concluded that Mir-425-5P could enhance osteoporosis in mice ( 94 ). The above studies indicate that the mechanism of miRNA action on osteoporosis still needs further study.…”
Section: Introductionmentioning
confidence: 99%